Soft skills elements in structured clinical skill assessment: a qualitative study - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin (2022)
Recognition of the importance of soft skills in the current healthcare setting has gained increasing momentum due to the high demand from society and employers.